Prediction and Management of Severe Acute Pancreatitis - Forsmark, Chris E.; Gardner, Timothy B. (Springer New York : Imprint: Springer, 2015)
This volume provides a comprehensive summary of pancreatitis and its complications, with expert recommendations on prediction and management. The text thoughtfully summarizes the current prediction models for severe acute pancreatitis, including laboratory, clinical and imaging parameters, and highlights the relative advantages and disadvantages of several of these models. Evidenced-based guidelines into medical and surgical management of both the hospitalized and discharged patient are described, with recommendations from expert authors pertaining to various clinical situations. The volume also discusses complications of acute pancreatitis and their management, including the use of cutting-edge minimally-invasive therapies. Prediction and Management of Severe Acute Pancreatitis serves as the fundamental source for those interested in and treating this disease, including practicing gastroenterologists, surgeons, radiologists, intensivists, hospitalists and pathologists.